Association of Men's Awareness of Danger Sign of Obstetric Complication and Male Involvement’s in Birth Preparedness Practices at South Ethiopia - Alemu Tamiso Debiso; Behailu Merdekios; Marelign Tilahun (International Journal of Public Health Science (IJPHS), 2015)
The Ethiopian Demographic and Health Survey (EDHS) indicate that maternal mortality in Ethiopia is one of the highest in the world. This death toll can be prevented partially through increasing awareness on danger sign of obstetric complications and birth preparedness practices for mother, husbands and other family members. Community based cross sectional study was done. Adult males with a wife or partner who had been through childbirth in the preceding 36 months were included in the study. Data was collected by pretested structured questionnaires and multi stage cluster sampling was used to reach 845 samples which were calculated by using StatCalc program of Epi Info 7. Collected data was cleaned and entered in to Epi Info 7 and exported to SPSS (IBM-20) for further analysis. Hierarchical logistic regression model and adjusted odds ratio with 95% confident interval were used to show association between men awareness and birth preparedness practices. The total numbers of men interviewed were 836 that makes response rate of 98.9%. Severe abdominal pain (87%) was the most recognized danger sign during pregnancy and 17.9% men involve in saving money.  Forty two point two percent of men had awareness of danger sign and 9.4 %( 95% CI: (7.42, 11.4) of men involved in birth preparedness practice. Strong association between men awareness of danger sign of obstetric complications and involvements in birth preparedness practices persisted after adjusting for probable confounders. Thus respondents who had awareness of danger signs were two times (AOR: 1.91, 95% CI: 1.06, 3.41) more likely to involve in preparedness practice than respondents who had no awareness of danger signs of obstetric complication. The prevalence of men awareness of danger sign & involvement in birth preparedness practice was very low.